"Showrooming" in Consumer Electronics Retailing: An Empirical Study. Issue 2 (3rd April 2017) - Rejón-Guardia, Francisco; Luna-Nevarez, Cuauhtemoc
ABSTRACT: The present study focuses on multichannel retailing strategies and describes the state of consumer behavior regarding "showrooming" (the practice of examining merchandise or products in a retail store and then buying it online). Founded on the theory of planned behavior (TPB), the authors examine the antecedents of showrooming using data collected from a sample of 176 retail consumers. Based on their results, they define perceived control, website compatibility, and subjective norms as the main antecedents of consumer attitudes toward online purchases. Additionally, they state that previous experience and reasons against purchasing online are directly associated with consumers' intention to purchase on the retailer's website. Finally, some theoretical conclusions and practical implications for retailers are discussed.